Upaya Pengembangan Usaha Pada UMKM Mebel Desa Nglebak Melalui Penerapan Digital Marketing - Kirana Aurelia Julianne Maharani; Naila Aisyah Putri; Yolanda Irfania; Mei Retno Adiwati (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Group KKN-T MBKM UPN "Veteran" East Java conducted digital marketing training and assistance to Mr. Suparno's MSMEs Furniture business located in Nglebak Village, Bareng District, Jombang Regency. The purpose of this community service activity is to develop Pak Suparno's furniture business by providing insight into marketing strategies that initially used traditional methods, changing along with existing technological developments. In solving the MSME furniture problem owned by Mr. Suparno, training methods and Focus Group Discussion (FGD) were used by providing material presentation on the importance of the role of digital marketing for the development of a business, providing tutorials for creating accounts on digital media such as Shopee and Instagram to market their products. With this community service activity, it is hoped that it can provide benefits for MSME actors in Nglebak Village, namely adding insight to develop their business by marketing and selling products through e-commerce and social media as a place to introduce products.